Correlation between Disclosure Status and Stress in Men who Have Sex with Men with HIV - Edianto Edianto; Agung Waluyo; Sri Yona; Ina Martiana (Jurnal Keperawatan Indonesia, 2020)
Men who have sex with men living with HIV (MSM-LWH) experience psychological and social issues, including depression, anxiety, fear of infecting others, frustration, and social isolation. They may also experience problems in their relationships due to a fear of social stigma, such as marital issues, family conflicts, a lack of family support, economic difficulties, and social rejection by the family. This research aimed to assess the relationship between HIV status disclosure and stress in MSM-LWH in Medan, Indonesia. Here, a cross-sectional design and the convenience sampling technique were used. A total of 176 respondents who were MSM, HIV positive, and residents of Medan City were included in this work. Data were collected by means of HIV Status Disclosure questionnaires and a Perceived Stress Scale (PSS). Overall, 70.9% respondents reported disclosing their status to others and approximately half revealed experiencing stress. Moreover, HIV status disclosure was significantly associated with stress (p= 0.025). This study reveals that HIV status disclosure may result in negative effects on MSMLWH, represent a barrier to medical treatment, and increase internal stress. Abstrak Hubungan antara Status Disclosure dengan Stres pada Lelaki yang Berhubungan Seks dengan Lelaki dengan HIV. Lelaki yang berhubungan Seks dengan lelaki (LSL) yang hidup dengan HIV mengalami masalah psikologis dan sosial termasuk depresi, kecemasan, ketakutan menulari orang lain, frustasi dan isolasi sosial. Selain itu juga mengalami masalah dalam hubungan sosial karena takut akan stigma, konflik dalam keluarga, kurangnya dukungan keluarga, kesulitan ekonomi dan penolakan oleh keluarga. Penelitian ini bertujuan untuk mengetahui hubungan antara status disclosure HIV dengan stress pada LSL yang hidup dengan HIV di Medan, Indonesia. Metode yang digunakan adalah cross-sectional dengan menggunakan teknik convenience sampling. Sebanyak 176 responden LSL dengan HIV positif dan tinggal di wilayah kota Medan. Data dikumpulkan dengan menggunakan HIV Status Disclosure Questionare dan Perceived Stress Scale (PSS). Hasil penelitian menemukan bahwa sebanyak 70,9% responden memiliki status disclosure HIV rendah, sementara itu sebanyak 55,1% resonden mengalami stress yang tinggi. Status disclosure HIV secara ber-makna dikaitkan dengan stress (p= 0,025). Penelitian ini mengungkapkan bahwa status disclosure HIV dapat mem-berikan efek negatif pada LSL yang hidup dengan HIV dan menjadi penghalang untuk perawatan medis dan mening-katkan stress internal.Kata Kunci: HIV, lelaki yeng berhubungan seks dengan lelaki, status disclosure, stres